THE FUNCTION OF METAPHOR, EPITHET AND OTHER STYLISTIC DEVICES IN THE TEXT - Farxadova Maftuna Umidjan qizi; Ruzmetova Diana Komilovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article examines the functional role of metaphor, epithet, and other stylistic devices  in  literary  and  non-literary  texts.  Stylistic  devices  are  not  only  decorative linguistic  elements  but  also  powerful  semantic  tools  that  shape  meaning,  create imagery, enhance emotional impact, and influence the reader’s perception. The study explores how these devices function within various textual contexts, including fiction, poetry, journalism, and public discourse. Special attention is given to their cognitive and communicative functions, the mechanisms of interpretation, and their contribution to coherence and expressiveness. The findings show that stylistic devices enrich the text  by  intensifying imagery,  building  associative  links, expressing  evaluation,  and deepening conceptual content.